Cryptocurrency Investment Risks and Perceived Usefulness: Basis of Cryptocurrency Risk Management Plan - Zamoras, John Michael J.; Dalumpines, Sheila S.; Refugio, Joseph G. (Center for Risk Management & Sustainability and RSF Press, 2024)
The surging popularity of cryptocurrencies presents both opportunities and challenges. While some view it as the future of finance, others remain concerned about investment risks. This uncertainty creates difficulties for consumers and financial institutions. To address this gap, the study assessed consumer perceptions of cryptocurrency investment risks and perceived usefulness, aiming to identify new avenues for transactions and investments. Employing a quantitative descriptive approach, a survey was conducted among 150 individuals from two (2) cities in the Philippines using a validated instrument and the Technological Acceptance Model (TAM). Results showed that consumers perceived moderate risk across trust, privacy, security, and financial aspects. No significant demographic variations were found in risk perception or perceived usefulness. These findings suggest a generally positive consumer attitude toward cryptocurrency investment despite the risks. This implies the possibility of widespread adoption if expectations align with the technology’s actual capabilities. Ultimately, this study offers valuable insights into consumer decision-making, which can inform future risk management strategies in the cryptocurrency landscape. It focuses on a geographically under-researched population (Philippines). This research contributes valuable insights for policymakers and industry leaders developing strategies to promote responsible cryptocurrency adoption across diverse user groups, particularly in emerging markets.